PENERAPAN STEGANOGRAFI LSB DAN KRIPTOGRAFI AES-256 DALAM KEAMANAN FILE GAMBAR - Suhada S. Yunus; Yohanes Suban Belutowe; Benyamin Jago Belalawe (Jurnal Publikasi Manajemen Informatika, 2026)
Digital data security has become a crucial aspect in an era where information exchange is increasingly open, especially within government institutions that handle sensitive internal documents and messages. In the context of the Military Court III-15 Kupang, a security mechanism is required to ensure the confidentiality and integrity of messages during internal data transmission. This study applies a combination of the Least Significant Bit (LSB) steganography method and the Advanced Encryption Standard 256-bit (AES-256) cryptographic algorithm to enhance the security of text messages. The text message is first encrypted using AES-256 to generate ciphertext, which is then embedded into a Portable Network Graphics (PNG) image by manipulating the least significant bits of its pixels using the LSB method. The result of this research is a web-based application implementing LSB steganography and AES-256 cryptography for securing image files, specifically designed to support the internal information security needs of the Military Court III-15 Kupang. The combination of both methods provides a dual-layer security mechanism, ensuring that the hidden message remains protected even if the image file is transferred or accessed by unauthorized parties.